2018
DOI: 10.3892/etm.2018.5939
|View full text |Cite
|
Sign up to set email alerts
|

ASXL1 mutations in Chinese patients with essential thrombocythemia

Abstract: Essential thrombocythemia (ET) is characterized by thrombotic and hemorrhagic events. The association of clinical characteristics of Chinese ET patients and additional sex combs like 1 (ASXL1) mutations in these patients has remained to be elucidated. In the present study, 72 newly diagnosed Chinese ET patients were enrolled to determine ASXL1 mutations. Mutations in ASXL1, Janus kinase (JAK)2, calreticulin (CALR) and myeloproliferative leukemia (MPL) genes were detected using Sanger sequencing, and data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The frequencies of ASXL1 mutations in PV, ET, and PMF were 3.5%, 5.6%, and approximately 23%, respectively [129,130,134]. In a Chinese cohort study [135], ASXL1 mutation was detected in 19.4% of patients with ET, where missense mutation (c.G1954A) was the most common mutation type. The frameshift mutation (c.1934dupG) was not detected in this cohort.…”
Section: Asxl1mentioning
confidence: 96%
See 1 more Smart Citation
“…The frequencies of ASXL1 mutations in PV, ET, and PMF were 3.5%, 5.6%, and approximately 23%, respectively [129,130,134]. In a Chinese cohort study [135], ASXL1 mutation was detected in 19.4% of patients with ET, where missense mutation (c.G1954A) was the most common mutation type. The frameshift mutation (c.1934dupG) was not detected in this cohort.…”
Section: Asxl1mentioning
confidence: 96%
“…ET patients harbouring the ASXL1-mutation are prone to experience thrombotic events, it can be postulated that ASXL1 mutations may partake in the occurrence of thrombohaemorrhagic events in ET. Although the relationship between ASXL1 mutations and the thrombotic pathogenesis of ET remains unclear, one study suggested that one of the potential strategies to prevent thrombotic events in patients with ET is through blocking the ASXL1 mutations [135]. Therefore, future studies are required to assess and evaluate the genetic contribution of ET in thrombosis.…”
Section: Asxl1mentioning
confidence: 99%
“…13 However, the association of non-driver gene mutations with thrombo-haemorrhagic events for ET has been inconclusive because several conflicting reports have been published. [14][15][16] Herein, we analysed non-driver gene mutations in 579 ET patients and evaluated the association of non-driver gene mutations with thrombo-haemorrhagic events.…”
Section: Impact Of Non-driver Gene Mutations On Thrombo-haemorrhagic ...mentioning
confidence: 99%
“…In recent years, the association between non‐driver gene mutations and prognosis has also been analysed in ET, and the mutation‐enhanced international prognostic systems for essential thrombocythaemia (MIPSS‐ET) incorporating SRSF2 , SF3B1 , U2AF1 and TP53 mutations has been proposed as a prognostic system for ET 13 . However, the association of non‐driver gene mutations with thrombo‐haemorrhagic events for ET has been inconclusive because several conflicting reports have been published 14–16 . Herein, we analysed non‐driver gene mutations in 579 ET patients and evaluated the association of non‐driver gene mutations with thrombo‐haemorrhagic events.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the recurrent somatic missense V617F mutation in the human Janus kinase 2 (JAK2) gene was identified in the granulocyte DNA samples collected from 37 of 115 ET patients by the genomic sequencing technique, which produced a constitutively active tyrosine kinase (Mela Osorio et al, 2016; Pósfai et al, 2015). Subsequently, mutations in other functional genes such as the MPL (myeloproliferative leukemia virus oncogene) encoding the thrombopoietin receptor and the calreticulin gene (CALR) which serves as a chaperone protein involved in protein folding inside the endoplasmic reticulum, were also shown to be associated with ET development (Guo et al, 2014; Nie et al, 2018; Pósfai et al, 2015; Rumi et al, 2014). Also, the mutation status in JAK2 and CALR genes were characterized as determinants for subtypes of ET, associated with the various clinical pathogenic course and treatment outcomes (Pósfai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%